2022
DOI: 10.3390/ani12202821
|View full text |Cite
|
Sign up to set email alerts
|

Specific Gene Duplication and Loss of Cytochrome P450 in Families 1-3 in Carnivora (Mammalia, Laurasiatheria)

Abstract: Cytochrome P450s are among the most important xenobiotic metabolism enzymes that catalyze the metabolism of a wide range of chemicals. Through duplication and loss events, CYPs have created their original feature of detoxification in each mammal. We performed a comprehensive genomic analysis to reveal the evolutionary features of the main xenobiotic metabolizing family: the CYP1-3 families in Carnivora. We found specific gene expansion of CYP2Cs and CYP3As in omnivorous animals, such as the brown bear, the bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 126 publications
1
2
0
Order By: Relevance
“…A phylogenetic analysis and synteny comparison of the CYP2C cluster region was conducted next (Figure 3). The coding loci of CYP2Cs were highly conserved between "helicase lymphoid specific (HELLS)" and the "PDZ and LIM domain 1 (PDLIM1)" (Figure 3A), as was also reported in a previous study [19,29]. The phylogenetic tree showed that CYP2C of elephants can be separated into five different groups; CYP2C19 (clade 1), another group of CYP2C19 (clade 2), CYP2C42 (clade 3), CYP2C21 (clade 4), and CYP2C23 (clade 5).…”
Section: Phylogeny Tree and Synteny Map Of Cyp2a 2c And 3asupporting
confidence: 80%
See 2 more Smart Citations
“…A phylogenetic analysis and synteny comparison of the CYP2C cluster region was conducted next (Figure 3). The coding loci of CYP2Cs were highly conserved between "helicase lymphoid specific (HELLS)" and the "PDZ and LIM domain 1 (PDLIM1)" (Figure 3A), as was also reported in a previous study [19,29]. The phylogenetic tree showed that CYP2C of elephants can be separated into five different groups; CYP2C19 (clade 1), another group of CYP2C19 (clade 2), CYP2C42 (clade 3), CYP2C21 (clade 4), and CYP2C23 (clade 5).…”
Section: Phylogeny Tree and Synteny Map Of Cyp2a 2c And 3asupporting
confidence: 80%
“…CYP2C23 are other genes found in elephants, several herbivores, and carnivores. The CYP2C23 of rats and mice are known as arachidonic acid or eicosanoid metabolizing CYPs [ 50 , 51 ], considered more like endogenous-metabolizing isoforms, which may play a similar role in these taxa [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation